Differences in Dental Arch Dimensions in a Sample of Kurdish Population among Different Occlusal Categories (Ex Vivo Study) - Rawand J. Othman; Hiwa S. Khidir (Polytechnic Journal)
It is essential to know dental arch dimensions to provide accurate diagnosis and treatment planning to ensure the satisfactory outcome of orthodontic treatment. The aim of the present study was to measure and compare dental arch dimensions of a Kurdish sample in Erbil city with normal and different classes of malocclusion. Arch width and length were measured by an electronic digital caliper on a total of 150 orthodontic models of school students aged 16–20 years of different occlusal relationships (Class I normal occlusion, Class I, Class II division I, Class II Division II, and Class III malocclusions). The results showed that (1) girls have smaller arch parameters than boys; (2) Class II division II malocclusion showed a significantly smaller upper inter canine width, arch length, incisor molar distance, and incisor canine distance when compared to all other groups; (3) the upper inter premolar and inter molar width were significantly narrower in Class II division I malocclusion than of normal occlusions and Class III malocclusion and also narrower in Class I malocclusion than in normal occlusions for both arches; (4) the arch length was significantly longer in Class II division I when compared to Class II division II, Class I malocclusions (P < 0.01), Class III malocclusion and Class I normal occlusion (P < 0.05), and (5) no statistically significant differences were found in all the arch dimensions for Class III malocclusion when compared with the normal occlusion. In conclusion, girls had smaller arch dimension than boys and Class II Division II malocclusion showed smaller arch in all dimensions while Class II division I malocclusion revealed narrower arch width and longer arch length.